Ahmadiyya Islam and the Muslim Diaspora Living at the End of Days - Balzani, Marzia (SEMPRE Studies in The Psychology of Music, 2020)
This book is a study of the UK-based Ahmadiyya Muslim community in the context of the twentieth-century South Asian diaspora. Originating in late nineteenth-century Punjab, the Ahmadis are today a vibrant international religious movement; they are also a group that has been declared heretic by other Muslims and one that continues to face persecution in Pakistan, the country the Ahmadis made their home after the partition of India in 1947. Structured as a series of case studies, the book focuses on the ways in which the Ahmadis balance the demands of faith, community and modern life in the diaspora. Following an overview of the history and beliefs of the Ahmadis, the chapters examine in turn the use of ceremonial occasions to consolidate a diverse international community; the paradoxical survival of the enchantments of dreams and charisma within the structures of an institutional bureaucracy; asylum claims and the ways in which the plight of asylum seekers has been strategically deployed to position the Ahmadis on the UK political stage; and how the planning and building of mosques serves to establish a home within the diaspora. Based on fieldwork conducted over several years in a range of formal and informal contexts, this timely book will be of interest to an interdisciplinary audience from social and cultural anthropology, South Asian studies, the study of Islam and of Muslims in Europe, refugee, asylum and diaspora studies, as well as more generally religious studies and history.